Effect of Exercise on Circulating Levels of Brain-derived Neurotrophic Factor (BDNF) in Overweight and Obese Subjects - Araya, A. V.; Orellana, X.; Godoy, D.; Soto, L.; Fiedler, J. (Hormone and Metabolic Research, 2013)
Exercise increases the expression of brain-derived neurotrophic factor (BDNF) in rodents and in healthy humans. Its relationship with weight loss and improvement in metabolic parameters, in obese human subjects, has not been elucidated. The aim of the study was to evaluate the effect of an aerobic exercise program on circulating levels of BDNF in overweight and obese subjects. We measured anthropometric and metabolic parameters in 15 male and female nondiabetic outpatients (age 38.3±9.5 years, BMI 27–35 kg/m2), before and after 30 sessions of aerobic exercise (3 sessions per week). Plasma (p), serum (s), and platelet (plat) BDNF concentrations were measured at basal condition and after completing 15 and 30 sessions of exercise. Subjects were advised to continue their usual food intake. A significant decrease in weight, BMI, waist circumference, diastolic blood pressure and total cholesterol was observed at the end of the study (p<0.02). Serum and platBDNF showed a significant increase during the training period (p=0.005 and 0.04 respectively). However, pBDNF showed no significant increase. Area under the curve of glucose at baseline, was inversely correlated with sBDNF (r= − 0.53, p=0.04) and platBDNF (r= − 0.6, p=0.01) after session 15. Also, platBDNF was correlated inversely with post load insulin and HOMA2-IR at the end of the training program (r= − 0.53, p=0.03 and r= − 0.52, p=0.04, respectively). In overweight and obese subjects, serum and platBDNF levels increase after 30 sessions of aerobic exercise. This is accompanied with the improvement of anthropometric and metabolic parameters and modest weight loss.